Commentary from Established Scholars: A man is not a tree, The Aftermath - Shomali, Farid (Advances in Social Sciences Research Journal, 2021)
In 30 June 2020, Dr. Farid Shomali, an architect meditating on current religion debates and human behaviors, was the first person on planet earth to reject the burial of the body in a peer review condensed two pages research paper or manifesto. While people from all thoughts and religions; the educated, the intelligent, the illiterate, even the rich and the broke practiced or witnessed that, in site or in media, from the beginning of creation tell now. His research paper: A man is not a tree will show you why GOD will never say to put people under the ground let alone cremate them, and how burial and cremation are deadly sins since GOD rejected it in his words, and practicing it will lead to complete destruction of Human thoughts and feelings. Then he tries to come up with his best solution. He is calling prohibiting burying and cremation the 11th commandment. The message must be spread to the entire world, so the Author encourages people to include his idea in religion debates, schoolbooks, university books, TVs, newspapers and manifestoes. Dr. Shomali while waiting for biblical institutions and all other religious institution in the whole world, to justify their position; telling us from where did they get this stupid and wrong idea called “burying” "you don't even bury a pencil, you bury a human!". Which is the most disgusting and stupid idea in the whole world that shows they got it wrong. He ask people to give him the Nobel peace prize for his research paper and if not the Templeton Prize or Pulitzer prize or at least a certificate from all of those recognized institutions and he also asks to announce June 30th 2020 a “no burial and no cremation day”- Note: no co-authors, Institutional or Influencers’ interventions